Radical architectural drawing - Spiller, Neil; Betsky, Aaron; Cantley, Bryan (Oxford John Wiley & Sons, Inc., 2022)
"There is a newfound interest in architectural drawing. Some of the most forward-looking architects worldwide are reinventing it to discover the radical possibilities of contemporary architecture as a rich mix of the virtual and the actual. Architectural drawing is adapting to compensate for these new changes to the discipline, and is being used to speculate on new paradigms of space and representation. This AD seeks to showcase the architects who are pushing the envelope of drawing in extraordinary ways, and their insights into architecture's future spatial dexterity. The issue is built around an international group of architects involved in an ongoing KU Leuven Faculty of Architecture international drawing research project, who are creating new drawing methodologies in new and exciting realms. Their projects are written about from the perspective of architectural representation by critics and commentators from across the globe, illustrating a cornucopia of graphic verve and talent in this highly contemporary and thought-provoking issue."
Keywords: Architectural drawing; Architectural drawing -- Research .; Architectural drawing -- Technique .; Architecture, Modern; Perspective